Framework for Institutional Shift of Service Infrastructure in Digital Economy - Vasily G. Zharov (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Digital services, platforms, ecosystems, and social networks integrate into the service infrastructure to form a new institutional environment. The current system of formal and informal rules fails to meet this challenge. Service consumers and providers demonstrate limited rationality and opportunistic behavior that prevent them from establishing trusting relationships. The increasing costs eventually result in low efficiency and uncertainty. The paper describes is to form the conceptual framework for the institutional environment of the service infrastructure in the context of digital economy. This framework relies on a rational combination of institutions and rules that make it possible to build economic relations on the trust between the service consumer and the service provider. The resulting economic ties form a self-regulating system based on mutual trust and a combination of formal and informal rules. The author used the institutional approach to study the stages of economic development in the sphere of service infrastructure. The analysis of customer/provider interaction scenarios in the context of limited rationality and opportunistic behavior made it possible to outline the target trajectory for the development of trusting relationships in digital economy and build itsconceptual model. The model is applicable to other social spheres associated with limited rationality and opportunistic behavior.